Hydraulic redistribution of foliar absorbed water causes turgor‐driven growth in mangrove seedlings. (22nd May 2019) - Schreel, Jeroen D.M.; Van de Wal, Bart A.E.; Hervé‐Fernandez, Pedro; Boeckx, Pascal; Steppe, Kathy
Abstract: Although foliar water uptake (FWU) has been shown in mature Avicennia marina trees, the importance for its seedlings remains largely unknown. A series of experiments were therefore performed using artificial rainfall events in a greenhouse environment to assess the ecological implications of FWU in A . marina seedlings. One‐hour artificial rainfall events resulted in an increased leaf water potential, a reversed sap flow, and a rapid diameter increment signifying a turgor‐driven growth of up to 30.1 ± 5.4 μm. Furthermore, the application of an artificial rainfall event with deuterated water showed that the amount of water absorbed by the leaves and transported to the stem was directly and univocally correlated to the observed growth spurts. The observations in this process‐based study show that FWU is an important water acquisition mechanism under certain circumstances and might be of ecological importance for the establishment of A . marina seedlings. Distribution of mangrove trees might hence be more significantly disturbed by climate change‐driven changes in rainfall patterns than previously assumed. Abstract : Although foliar water uptake has been shown in mature Avicennia marina trees, the importance for its seedlings remains largely unknown. Controlled greenhouse experiments indicated that foliar water uptake resulted in an increased leaf water potential, a reversed sap flow, and a rapid diameter increment signifying a turgor‐driven growth of up to 30.1 ± 5.4 μm. The observations in this process‐based study show that foliar water uptake is an important water acquisition mechanism under certain circumstances and might be of ecological importance for the establishment of A . marina seedlings.